Use of Saccharomyces cerevisiae to suppress the effects of ochratoxicosis in broiler chickens - SINGH, MOHIT; SINGH, RAM; MANDAL, A B (The Indian Journal of Animal Sciences, 2016)
In the present study, effect of inclusion of Saccharomyces cerevisiae (SC) in ochratoxin A (OTA) contaminated diet to ameliorate ochratoxicosis in broiler chickens was investigated. Day-old broiler chicks (240) were divided into 6 treatment groups (T1, control; T2, T1 + 200 ppb OTA; T3,T1 + 0.05% SC; T4, T1 + 0.1% SC; T5, T2 + 0.05% SC; T6, T2 + 0.1% SC). Each diet was fed to 5 replicated groups of 8 birds each from 0 to 42 days of age. During overall growth period (0–6 weeks), the body weight gain (BWG) of birds in ochratoxin alone fed group (T2) was lower than that of control group (T1). The BWG of group T5 was higher than T2 but lower than that of control (T1) indicating that addition of S. cerevisiae at 0.05% level partially ameliorated the adverse effects of ochratoxicosis on BWG of birds. The BWG in group T6 was higher than T2 and statistically equal to that of control, indicating that addition of S. cerevisiae at 0.1% level to the ochratoxin contaminated feed ameliorated the adverse effects of ochratoxin on BWG. Ochratoxin contamination in diet caused significant reduction in feed intake. Addition of S. cerevisiae to the ochratoxin contaminated feed ameliorated the adverse effects of ochratoxicosis on feed consumption. During 0–6 weeks of age, the FCR of control group (T1) was lower than that of ochratoxin alone fed group (T2). Ochratoxin (200 ppb) contamination of broiler diet caused higher mortality compared to control. Inclusion of S. cerevisiae (0.1%) to the ochratoxin contaminated feed improved FCR and reduced mortality. Supplementation of 0.1% S. cerevisiae to the 200 ppb OTA contaminated diet also resulted in significant improvement in the relative weight of liver and bursa. It was concluded that 200 ppb ochratoxin in broiler diet impaired the production performance in terms of body weight gain, feed intake, feed conversion efficiency, mortality and relative organ weights. Incorporation of 0.1% S. cerevisiae to the ochratoxin contaminated diet ameliorated the ill effects of ochratoxicosis as evidenced through production performance and relative weight of organs during 0–6 weeks of age in broiler chickens.